Geosynthetic-Reinforced Soil Structure Built to Restore Original Geometry of a 12 m High Slope After Failure Using Local Soil - Nunes De Franca, F. A. [UNESP]; Pereira, V. R. G. (Destech Publications, Inc, 2013)
This paper presents a study case in which a geosynthetic-reinforced soil (GRS) structure was used to rebuild a 12 m high slope after its failure. The failed slope is located between the parking lot of a private company and a public school. Due to surrounding structures restrictions, this project required a solution with rapidity in execution. In addition, as a requirement established by its owner, this structure should recover the original geometry of the slope. Besides the importance regarding surrounding constructions, an interesting aspect of this study case relies on the versatility of geosynthetic materials. A woven geotextile was used as reinforcement. Five other geosynthetic materials were used in this study case. Facing comprised a geocell filled with local soil cover and grass mats, resulting in a green facing. A geonet was used to hold the grass mats in place before grass roots development. Regarding the drainage system, geocomposite drains and geopipes were installed to drain subsurface water. A nonwoven geotextile was used as filter in drainage trenches, which were placed near the structure toe. Additionally to the GRS structure, the lower portion of the slope was reinforced with soil nailing technique. The face of the nailed soil portion was covered with sandbags and shotcrete. It emphasizes the flexibility of GRS structures regarding their application with other technical options in Geotechnical Engineering. The economic aspect of this study case also deserves attention. It did not require soil transportation and other design and construction steps, e.g. concrete structures design and construction.